PENGARUH PEMBELAJARAN ACTIVE LEARNING TTQ TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN PENGETAHUAN PRODUK - Sumarni, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract The problem in this research is the low of learning outcomes and student attention on the subjects of product knowledge class XI PM in SMKN 3 Pontianak. The method used in this study is an experimental method using quasi-experimental design to study design nonequivalent control group design. Subjects in this study were students of class XI PM2 and XI PM3 SMK Negeri 3 Pontianak with the number of 63 students. The results showed that the learning outcomes of the experimental class is higher than the control class for improving student learning outcomes larger experimental class is 28.86 while the control class only increased by 9.93. Based on the results of t-test experimental class and control class obtained t count > t table (3.013> 2.00), then Ho is rejected and Ha accepted. Thus, we can conclude Learning Model active learning type team quis no effect on student learning outcomes in subjects in class XI product knowledge PM SMK Negeri 3 Pontianak. Keywords: Active Learning TTQ, Learning Outcomes, Lessons Knowledge Products.